El control interno y la gestión administrativa, en un municipio de la Región Tacna - Candia Gutierrez, Rudy Narciso (2022)
The main objective of this study was to determine to what extent internal control influences administrative management in the district municipality of Pocollay, Tacna Region, year 2019. The type of research of this study is basic, its research design is non-experimental, and its explanatory level. The research was aimed at 30 workers; the content validity and reliability of each instrument was carried out, being of high reliability. The ordinal regression statistic was used to analyse the influence of internal control on the business management of the district municipality of Pocollay, with the Nagelkerke coefficient showing the influence of internal control of 65.0 % on administrative management. With respect to the level of influence of the dimensions of the internal control variable on administrative management, through the testing of hypotheses, by means of inferential statistics, influences were verified in values from the lowest to the highest in the range of 25.10% to 47%.